The desert realm lands of majesty and mystery - Eigeland, Tor; Bohong, Jin (National Geographic Society, 1982)
A portrait of the world's deserts highlights desert inhabitants, wildlife, plants, ecology, and culture, accompanied by over 300 color photographs.